THE CULINARY LEXICON OF PESISIR COMMUNITIES IN BARUS, CENTRAL TAPANULI: PERSPECTIVE OF ECOLINGUISTICS - Fatimah Sari Siregar; Yayuk Hayulina Manurung; Dharmawati Dharmawati (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2024)
Abstract: This article describes the culinary lexicon of the Pesisir communities in Barus, central Tapanuli from an ecolinguistic perspective. One of the environmental vocabulary which is a cultural nuance in society is the culinary lexicon. The culinary eco-collection is part of the local language vocabulary that is full of cultural wisdom that has existed since centuries ago and still exists today, and has a reciprocal relationship between language and its environment, both on a macrocosmic and microcosmic scale. The culinary lexicon of the Barus coastal community, Central Tapanuli Regency is classified into two lexicon groups, namely the lexicon of tools and materials and the lexicon of processing methods. From the two lexicon groups, 91 lexicon were obtained, consisting of 71 tools and materials lexicon, and 20 lexicon of processing. Pesisir communities in Barus describes culinary types based on sociological and biological dimensions. Sociologically, it is still a culinary dish that is still served if a guest comes to respect the guest. Keywords: Culinary lexicon; Ecolinguistics; Pesisir communities. Abstrak: Artikel ini mendeskripsikan leksikon kuliner masyarakat Pesisir di Barus, Tapanuli Tengah dari perspektif ekolinguistik. Salah satu kosakata lingkungan hidup yang menjadi nuansa budaya masyarakat adalah leksikon kuliner. Eco-collection kuliner merupakan bagian dari kosakata bahasa daerah yang sarat dengan kearifan budaya yang telah ada sejak berabad-abad yang lalu dan masih eksis hingga saat ini, serta memiliki hubungan timbal balik antara bahasa dan lingkungannya, baik dalam skala makrokosmik maupun mikrokosmik. Leksikon kuliner masyarakat pesisir Barus Kabupaten Tapanuli Tengah digolongkan ke dalam dua kelompok leksikon, yaitu leksikon alat dan bahan serta leksikon cara pengolahan. Dari kedua kelompok leksikon tersebut diperoleh 91 leksikon yang terdiri dari 71 leksikon alat dan bahan, serta 20 leksikon pengolahan. Masyarakat Pesisir di Barus mendeskripsikan jenis kuliner berdasarkan dimensi sosiologis dan biologis. Secara sosiologis, kuliner tetap merupakan kuliner yang tetap dihidangkan jika ada tamu yang datang untuk menghormati tamunya. Kata kunci: Leksikon Kuliner; Ekolinguistik; Masyarakat Pesisir.